Pre-injection magnetotelluric surveys at the Aquistore CO2 sequestration site, Estevan, Saskatchewan, Canada. (July 2018) - McLeod, Joe; Ferguson, Ian; Craven, Jim; Roberts, Brian; Giroux, Bernard
Graphical abstract: Highlights: MT response is 1D but spatially variable at <0.01 s, 1D at 0.01–10 s, 2D at >30 s. The MT model depends on the longitudinal resistivity of strongly stratified units. Noise includes 60 Hz harmonics and, in 2014, a source associated with CO2 pipeline. MT response is minimally sensitive to a CO2 plume at reservoir depth. Controlled-source responses at 9.5 km offset have maximum sensitivity at 0.5 Hz. Abstract: Magnetotelluric (MT) soundings were conducted in a 4 × 4 km area at the Aquistore CO2 sequestration site at Estevan, Saskatchewan, Canada in 2013, 2014 and 2015, prior to CO2 injection. The MT response is locally one-dimensional but spatially variable at short periods (<0.01 s), regionally one-dimensional at intermediate periods (0.01 s to 10 s), and two-dimensional at long periods (>30 s). Responses corresponding to Williston Basin rocks are uniform across the area. A representative MT response was inverted using constraints derived from a resistivity well-log. Beneath the Jurassic Watrous to Vanguard formations (at depths greater than 1240–1600 m), the resistivity of the inversion model is consistently 20–30% lower than in the reference well-log model, consistent with the MT method sensing the longitudinal resistivity of the more strongly stratified units at these depths. Electromagnetic noise in the MT data set includes high-frequency odd harmonics of the 60 Hz source and a broad-band source, spatially associated with the CO2 pipeline, observed only in 2014. Within the period range 10 −4 to 10 2  s, but outside the bands influenced by the broad-band noise, the off-diagonal MT impedance response at Aquistore can be measured with an RMS repeatability of 1% or better.